Odontidium andinum spec. nov. (Bacillariophyta) from Mendoza, Argentina - Sala, Silvia E.; Vouilloud, Amelia A. (Phytotaxa, 2018)
The genus Odontidium is characterized by the presence of robust internal transapical ribs, a wide sternum and a complex cingulum composed by several open bands with ligulae, differentiated in copulae and pleurae. Only two species of Odontidium have been recorded from Argentina. In samples collected in the upper basin of the Diamante River, Mendoza Province the dominant specimens were of this genus but differed from those species already known. Examination of the valve morphology of these specimens, and comparison with other species of the genus, showed it is a new species Odontidium andinum. O. andinum has valves broadly lanceolate to linear with rounded to subcapitate ends. It is similar to O. hyemale, O. mesodon and O. rostratum. Although smaller specimens of all these species are similar when using the light microscope, with a complete size series it is possible to see marked differences in the valves’ outline. These differences correspond with others found in the fine structure of the valves and girdles. These specimens also match those previously named as Diatoma hyemalis (Roth) Heiberg sensu lato, collected in the Chilean Andes and with others recently found in a high altitude river in Argentinean Patagonia, showing the Andean distribution of the species.